Negotiating Islamic Identity Through Cultural Adaptation: A Fiqh al-Aqalliyyat Analysis of Masselle aseng Practice in Indonesian Muslim Minorities - Nur, Muhammad Tahmid; Rismawati, Rismawati; Amirullah, Amirullah; Wagay, Javaid Ahmad; Nurdin, Elmiati (Jurnal Ilmiah Al-Syir'ah, 2025)
This research analyzes the negotiation of Islamic identity through adaptation of the masselle aseng tradition (name-changing ritual) in Indonesian Muslim minority communities using the fiqh al-aqalliyyat framework. Using a comparative ethnographic approach, the research was conducted in three locations: Teteuri Village, North Luwu (Muslim majority context); Bugis Village, Singaraja, Bali (Muslim minority in Hindu majority); and Bugis Village, Ambon (post-conflict multireligious context). Data were collected through in-depth interviews with 18 key informants, participant observation, document analysis, and interfaith dialogue. Findings reveal a three-stage evolution model: Pure Form in a homogeneous context (Luwu), Syncretistic Fusion through interfaith collaboration (Bali), and Universalistic Translation with neutral framing (Ambon). Demographic factors, cultural compatibility, historical context, and social integration need to be systematically considered in adaptation strategies. Islamic legal validation through 'urf sahih principles evolves from internal mechanisms to collaborative authority involving non-Muslim perspectives. Interfaith dynamics produce three engagement models: separation, active collaboration, and diplomatic neutrality. The research contributes to the fiqh al-aqalliyyat theory through the development of a dynamic authenticity framework that positions adaptation as a sophisticated survival strategy for maintaining traditional continuity while achieving social integration. This framework has broad applicability for global Muslim minority communities in navigating cultural preservation challenges and social harmony.